A new species of Megaesthesius Rathbun, 1909 (Crustacea: Brachyura: Chasmocarcinidae) from deep water off Western Australia - Davie, Peter J.f. (Zootaxa, 2013)
A new species of Megaesthesius Rathbun, 1909, M. westralia, is described from shelf waters off Western Australia. It can be separated from its two congeners by differences in carapace shape and dentition, as well as differences in the male ab-domens and gonopods.